The Influence of Supplementary Feeding (Probiotic and Azolla pinnata) on Protein and Amino Acids Content in Patin Fish - Ika Oktavianawati; Meirinda Hermiastuti; Novita Rahmawati; Wuriyanti Handayani; I Nyoman Adi Winata (UNEJ e-Proceeding, 2014)
One of the important factors in fish farming is feeding. Feed intake is able to affect the growth and production of fish, especially on nutritional content such as protein. In this research, Patin (Pangasius djambal), a catfish, were given variations in feed, i.e pellets only (P1) as a control; pellets and probiotic (P2); pellets and Azolla pinnata (P3). A. piñata (known locally as matalele) is a water plant that has complete essential amino acids including threonine, valine, methionine, isoleucine, leucine, phenylalanine, lysine, histidine, arginine and tryptophan. Probiotic is living microbial cells that affects the speed of feed fermentation and helps the absorption of food in the gastro intestinal tract. The results show that P2 gains more weight than P1 and P3. This feed variations also give different levels of crude protein in fish meat P1, P2, and P3 that are in the order 14.62%; 15.74%; and 13:35%. Based on the results of LC-MS analysis, the amount and the dominant amino acids content in the protein of P1, P2, and P3 are 13 amino acids–aspartic acid; 13 aminoacids–glutamic acid; and 14 amino acids and is predominantly asparagine. Keywords: protein, amino acid, patin, probiotic, Azolla pinnata